A study of lipid profile in patients of subclinical hypothyroidism in rural area of Western Uttar Pradesh, India - Kumar, Manoj; Rajpoot, Raveendra S. (International Journal of Research in Medical Sciences, 2017)
Background: Dyslipidemia is thought to confer risk of cardiovascular disease development. Overt hypothyroidism is associated with lipid abnormalities. However, the relationship between subclinical hypothyroidism (SCH) and pattern of lipid abnormalities is unclear. The aim of this study was to assess lipid abnormalities in patients of subclinical hypothyroidism (SCH) and investigate relationship between lipid level and TSH. Methods: Serum lipid levels of 87 patients with subclinical hypothyroidism (SCH) and 101 age and sex matched euthyroid controls were evaluated in this cross sectional case control study. Results: In this study total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) were significantly elevated (p value<0.05) in patients with subclinical hypothyroidism (SCH) as compared to control group. Triglycerides (TG) and very low density lipoprotein cholesterol (VLDL-C) were also high in these patients as compared to control but the difference was not statistically significant. High density lipoprotein cholesterol (HDL-C) was marginally lower in these patients than control. Conclusions: Total cholesterol (TC) and low density lipoprotein (LDL-C) are higher in patients with subclinical hypothyroidism (SCH) as compared to euthyroid individuals. Other lipid like Triglycerides (TG) and very low density lipoprotein cholesterol (VLDL-C) may be marginally elevated whereas high density lipoprotein cholesterol (HDL-C) may be slightly reduced in these patients as compared to euthyroid individuals. There is also a positive correlation of LDL-C and TC with TSH level. As abnormal lipids are associated with development of cardiovascular diseases, lipid profile in these patients needs careful monitoring.